(untitled) (Nepal Journal of Epidemiology, 2020)
Background: Diabetes Mellitus (DM) causes micro and macro vascular complications. One of the complications of DM is diabetic foot that results in amputations and decreased quality of life. The aim of this study was to assess the awareness and practice about foot care and associated factors among admitted patients in a teaching hospital of coastal Karnataka, India. Material and Methods: A cross-sectional study was conducted in a medical college hospital after obtaining institutional ethics approval from 24th December 2016 to 21st January 2017. Adults with diabetes (N=317) admitted in the hospital were interviewed with a validated structured questionnaire for awareness and practice regarding foot care. The scores obtained were further graded into good and poor. Data was analyzed with SPSS version 22 for descriptive statistics. Bivariate logistic and linear regressions were used to determine the association between variables and awareness/ practice scores. Results: Mean age of the participants was 56.98 (±10.54) years with males constituting the majority (63.4%). Good awareness and practice scores were observed among 69.1% and 41.6% participants, respectively. Good awareness scores were associated with male patients (p=0.027), currently not married (p=0.044), below poverty line socioeconomic status (p=0.014) and presence of foot ulcer (p=0.021). Good practice scores was associated with secondary schooling (p=0.003) and receiving insulin (p=0.045). Moderate correlation with coefficient 0.493 (p<0.001) was observed between awareness and practice scores. Conclusion: Seven and four out of 10 study participants had good awareness and practice scores about foot care, respectively. A tailor-made health education module addressing the lacunae identified in the awareness and practice domains needs to be provided to the patients with diabetes mellitus.